Cadmium delays puberty onset and testis growth in adolescents. (15th January 2015) - Interdonato, Monica; Pizzino, Gabriele; Bitto, Alessandra; Galfo, Federica; Irrera, Natasha; Mecchio, Anna; Pallio, Giovanni; Ramistella, Vincenzo; Luca, Filippo De; Santamaria, Angelo; Minutoli, Letteria; Marini, Herbert; et al.
Summary Objective Cadmium (Cd) has been shown to impair pubertal development in experimental animals. However, no data are available for male adolescents with increased urinary cadmium levels. Design The aim of this cross‐sectional study was to evaluate pubertal onset and pituitary–gonadal axis hormones in male adolescents with increased urinary levels of Cd. Subjects We studied 111 males, aged 12–14 years living in the Milazzo‐Valle del Mela area. A control age‐matched population (n = 60) living 28–45 km far from the industrial site was also enrolled. Measurements Pubertal stages were assessed by clinical examination according to Tanner's score. Mean testicular volume was also investigated by ultrasound examination. Urinary Cd concentration and blood levels of FSH, LH, testosterone and inhibin B were also investigated. Results Cd levels were significantly higher in adolescents living in the Milazzo‐Valle del Mela area, compared to both age‐matched subjects living far from the industrial plants and the reference values. Our population showed also a delayed onset of puberty, a smaller testicular volume and lower testosterone levels. An inverse correlation was found between urinary Cd and testicular volume (r = −0·25; P = 0·0008), testosterone levels (Spearman's r = −0·0·37; two‐tailed P < 0·0001) and LH levels (Spearman's r = 0·048; P < 0·05). Testosterone levels were positively correlated with testicular volume (Spearman's r = 0·48; P < 0·0001). Conclusions This study, for the first time, suggests that increased Cd burden is associated with delayed onset of puberty in male adolescents and impaired testicular growth.